PB ISOTOPIC AND ELEMENTAL EVIDENCE FOR OIB DERIVATION FROM YOUNG HIMU MANTLE - Thirlwall M.F. (My University, 1997)
Isotopic variation in ocean island basalts (OIB) is commonly attributed to mixing between four distinctive isotopic components in the mantle. One of these, HIMU, is the only contributor of lead with 206Pb/204Pb > 19.2 to the system and is therefore invoked as a mixing component in very many OIB. Extreme HIMU mantle, as represented by OIB with206 Pb/204Pb > 20.5, must have been generated by elevated 238U/204Pb ratios (μ values) over time periods of 1.5-2 Ga. If high μ also developed in mantle much more recently than 1.5 Ga, then its isotopic results today could broadly simulate mixtures between extreme HIMU and the other isotopic components.207Pb/204Pb ratios lying systematically below the Northern Hemisphere Reference Line and the MORB data field are quite common in ocean island basalts. These are described as negative-Δ7/4Pb OIB, and have fairly homogeneous compositions for other isotopic systems, and similar trace element characteristics to the extreme HIMU OIB from St. Helena and the Cook-Austral Islands, including low K/Nb and Ba/Nb ratios, but high Ce/Pb and μ values. These compositions can be generated during the Phanerozoic and Proterozoic from mantle with chemical characteristics similar to those of the mantle source of extreme HIMU lavas. A μ value of 20 +/- 2 is estimated for the HIMU source and used to model the source of negative-Δ7/4Pb OIB. These OIB are most unlikely to be produced by:(1) Mixing between MORB and HIMU mantle, both because this cannot generate negative Δ7/4Pb, and because they have elevated 87Sr/86Sr and Δ8/4Pb relative to MORB-HIMU mixtures, but high Ce/Pb and low Ba/Nb that do not permit admixture of any enriched component.(2) Ageing of the observed high μ values in the oceanic lithosphere, because there is no relationship between the age of the lithosphere, the magmatic μ value and the extent of negative Δ7/4Pb. Further, μ is shown to be substantially increased during the melting process.Ce is shown to be more incompatible than Pb during melting in most negative-Δ7/4Pb OIB suites, and in some MORB and extreme HIMU suites. Higher Ce/Pb ratios in HIMU and negative-Δ7/4Pb OIB than in MORB may just reflect the melting process. There is thus no compelling evidence that the increased μ of HIMU mantle is due to depletion in Pb relative to MORB mantle. Ratios involving K and Nb appear to be frequently fractionated by a potassic phase such as phlogopite in the source. Higher Ce/Pb and Nd/Pb in negative-Δ7/4Pb OIB than in extreme HIMU OIB cannot be generated by melting, and along with the elevated 87Sr/86Sr and Δ8/4Pb, probably reflect secular changes in the process that generates HIMU mantle.Most negative-Δ7/4Pb OIB could be derived from fairly pure young HIMU mantle. Large volumes of continental and oceanic basalts with similar isotopic and chemical signatures, apart from zero or slightly positive Δ7/4Pb, merely require minor incorporation of enriched components (crust or mantle) into melts derived from young HIMU mantle. Recognition of this as a major mantle reservoir would eliminate the need for MORB-source mantle contributions to most OIB.
Keywords: PB; OIB DERIVATION; HIMU MANTLE